Gandang Tambua Pariaman From Triplek Material an Organological Study Based on Coding - Wimbrayardi Wimbrayardi; Bambang Parmadi; Irdhan Epria Darma Putra; Wembrayarli Wembrayarli (Mudra Jurnal Seni Budaya, 2023)
The process of making the Gandang Tamba traditional musical instrument in Padang Pariaman Regency. This study aims to describe the process of making the Gandang Tamba musical instrument. The approach used is a qualitative approach with a descriptive research type. This research was conducted with data collection techniques using observation, interview, and documentation techniques. Data analysis techniques are carried out by reducing, presenting data and verifying data. The aim is to find out the structure, process, manufacturing techniques, and playing techniques, of Gandang Tamba. This musical instrument is made of plywood and has a hole (resonator), and uses goat skin. The results of this study indicate that the parts and stages of the process of making traditional Gandang Tambua musical instruments include: cutting plywood for the body of Gandang Tambua, processing goat skin (membrane), cleaning rattan, making iron battens, and how to produce sound, tuning system on traditional Gandang musical instruments Tambua. The tools used in the process of making traditional Gandang Tambua musical instruments include: Cater knives (plywood cutters), Cutting Saws, Hammers (Penokok), Measuring tools (meters), Pencils, Sandpaper, Screwdriver, Scissors, Bamboo type gutters, and Tongs. The ingredients are; Wooden battens (circle 40), plywood, goat skin, iron lath, rope, nails, and wood glue. The process of making the Gandang Tambua musical instrument includes several stages, namely: 1) The process of making the body (plywood), to the finishing of fine and coarse sanding, 2) The processing of the skin, including the shearing of the skin using dry fuel ash and measuring the width of the diameter, 3) The installation process, includes the skin to the body of the Tambua drum, attaching iron battens and attaching strings as for tuning. The frequency and tension of each instrument membrane on the Gandang Tambua musical instrument, the membrane tension of 141090.66 N on the Gandang Tambua musical instrument produces good tension (tuning), because the vibrations of the membrane will fill the resonance space in the drum tube. While the membrane tension of 131841.38 N produces poor tuning, the vibration of the membrane does not meet the resonance chamber. attach the iron battens and attach the rope for tuning. The frequency and tension of each instrument membrane on the Gandang Tambua musical instrument, the membrane tension of 141090.66 N on the Gandang Tambua musical instrument produces good tension (tuning), because the vibrations of the membrane will fill the resonance space in the drum tube. While the membrane tension of 131841.38 N produces poor tuning, the vibration of the membrane does not meet the resonance chamber. attach the iron battens and attach the rope for tuning. The frequency and tension of each instrument membrane on the Gandang Tambua musical instrument, the membrane tension of 141090.66 N on the Gandang Tambua musical instrument produces good tension (tuning), because the vibrations of the membrane will fill the resonance space in the drum tube. While the membrane tension of 131841.38 N produces poor tuning, the vibration of the membrane does not meet the resonance chamber.